The Influence of Inclusive Leadership on Lecturer Performance Through SWOT Analysis: Leader-Member Exchange as a Mediating Variable at Private Universities in Indragiri Hilir Regency - Syafrinadina, Syafrinadina; Havidz Aima, M. (Siber International Journal of Digital Business (SIJDB), 2024)
This study examines the impact of inclusive leadership on lecturer performance through a SWOT analysis, with Leader-Member Exchange (LMX) as a mediating variable at private universities in Indragiri Hilir Regency. The research aims to determine how inclusive leadership fosters a supportive work environment, enhances lecturer motivation, and ultimately improves performance. Using a combination of qualitative and quantitative methods, the study analyzes the strengths, weaknesses, opportunities, and threats associated with inclusive leadership and its effect on LMX quality. The findings indicate that inclusive leadership significantly enhances lecturer performance by creating a positive LMX, thereby fostering higher motivation, commitment, and job satisfaction. The study also highlights potential challenges, such as resistance to change and the need for continuous training. These insights are crucial for academic institutions aiming to enhance their educational quality through effective leadership practices.